ECONOMIC PREREQUISITES FOR THE DEVELOPMENT OF THE ECOLOGICAL CULTURE OF FUTURE TRANSPORT PROFESSIONALS - M. Klymenko; L. Bazyl; V. Orlov; T. Rulievska (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The aim of the article is to study the economic prerequisites for the development of ecological culture of future transport professionals and analyze foreign experience of ecological education of students to adapt their best practices to Ukrainian realities and productive use of achievements in training future transport professionals.